Neurocognitive functioning and health-related quality of life in patients treated with stereotactic radiotherapy for brain metastases: a prospective study. Issue 3 (18th September 2015) - Habets, Esther J.J.; Dirven, Linda; Wiggenraad, Ruud G.; Verbeek-de Kanter, Antoinette; Lycklama à Nijeholt, Geert J.; Zwinkels, Hanneke; Klein, Martin; Taphoorn, Martin J.B.
Abstract: Background: Stereotactic radiotherapy (SRT) is expected to have a less detrimental effect on neurocognitive functioning and health-related quality of life (HRQoL) than whole-brain radiotherapy. To evaluate the impact of brain metastases and SRT on neurocognitive functioning and HRQoL, we performed a prospective study. Methods: Neurocognitive functioning and HRQoL of 97 patients with brain metastases were measured before SRT and 1, 3, and 6 months after SRT. Seven cognitive domains were assessed. HRQoL was assessed with the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 and BN20 questionnaires. Neurocognitive functioning and HRQoL over time were analyzed with linear mixed models and stratified for baseline Karnofsky performance status (KPS), total metastatic volume, and systemic disease. Results: Median overall survival of patients was 7.7 months. Before SRT, neurocognitive domain and HRQoL scores were lower in patients than in healthy controls. At group level, patients worsened in physical functioning and fatigue at 6 months, while other outcome parameters of HRQoL and cognition remained stable. KPS < 90 and tumor volume >12.6 cm 3 were both associated with worse information processing speed and lower HRQoL scores over 6 months time. Intracranial tumor progression was associated with worsening of executive functioning and motor function. Conclusions: Prior to SRT, neurocognitive functioning and HRQoL are moderately impaired in patients with brain metastases. Lower baseline KPS and larger tumor volume are associated with worse functioning. Over time, SRT does not have an additional detrimental effect on neurocognitive functioning and HRQoL, suggesting that SRT may be preferred over whole-brain radiotherapy.